Traditional honey production and bee flora of Espiye, Turkey (Bangladesh Journal of Plant Taxonomy, 2018)
This paper presents potential honey bee plants in Espiye (Giresun) which can be considered as a guide for beekeepers and researchers. A total of 149 taxa belonging to 125 genara and 48 families were recorded as pollen and nectary sources for honey bee colonies at Espiye (Giresun) region. Among the recorded taxa 58 were Phanerophytes, 57 taxa Hemicryptophytes, 19 taxa Therophytes, 13 taxa Cryptophytes and 2 taxa Chamaephytes. Updated nomenclature along with the families, local names, life form, flowering period and ecological status have been furnished under 94 herbs, 28 shrubs and 27 trees.Bangladesh J. Plant Taxon. 25(1): 79-91, 2018 (June)